The Effect of Keroncong Music Therapy on Reducing Agitation in the Elderly with Dementia - Dhita Kurnia Sari; Jimni Maulana; Sismulyanto; Bibi Amikasari (Journal of Global Research in Public Health, 2022)
Dementia naturally occurs along with the aging process, the thing that is most avoided from the symptoms of dementia is agitation. This condition causes feelings such as irritation or excessive anxiety. This can trigger a decline in intellectual capacity which is characterized by cognitive, emotional, and psychomotor disturbances. A continuous therapy with minimal side effects is required before the use of medical therapy which is known to be high in side effects. This study aims to analyze the effect of keroncong music therapy in reducing the level of agitation in the elderly with dementia. Elderlies with dementia using simple random sampling technique. The sample was divided into 29 treatment groups and 29 control groups. The statistical test used was Mann-Whitney. The treatment group was given keroncong music therapy at a dose of 15 minutes a day for 14 consecutive days. At the pre-test, there was no significant difference in agitation levels between the two groups (p=0.748), but at the post-test, a significant difference in agitation levels was found between the two groups (p <0.05). Keroncong music therapy can reduce the level of agitation in the elderly with dementia. Future researchers are expected to be able to conduct research by comparing the effectiveness of keroncong music therapy with other non-pharmacological interventions in reducing agitation levels.